Reinventing Modernity in Latin America Intellectuals Imagine the Future, 1900-1930 - Miller, N. (Studies of the Americas, 2008)
This is an exploration of how Latin America developed an alternative modernity during the early twentieth century, one that challenges the key assumptions of the Western dominant model.